2007
DOI: 10.1016/j.physbeh.2007.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Chronic psychological stress enhances nociceptive processing in the urinary bladder in high-anxiety rats

Abstract: This study sought to determine whether acute and/or chronic psychological stress produce changes in urinary bladder nociception. Female Sprague-Dawley (SD; low/moderate anxiety) or WistarKyoto (WK; high-anxiety) rats were exposed to either an acute (1 day) or a chronic (10 days) water avoidance stress paradigm or a sham stress paradigm. Paw withdrawal thresholds to mechanical and thermal stimuli and fecal pellet output, were quantified at baseline and after the final stress or sham stress exposure. Rats were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 42 publications
6
74
1
3
Order By: Relevance
“…Thus future studies should be pursued in anesthetized rats where potential effects of the outlet including the urethra and EUS can be evaluated after RVS. RVS-induced increases in voiding frequency are similar to other reports regarding several other animal models of stress including social defeat (4,15,46,74), nontraumatic immobilization/restraint (11,74), and WAS (14,54,62). We suggest that the 7-day RVS model has several advantages compared with other stress models.…”
Section: Rvs Induces Changes In Urinary Bladder Functionsupporting
confidence: 87%
See 1 more Smart Citation
“…Thus future studies should be pursued in anesthetized rats where potential effects of the outlet including the urethra and EUS can be evaluated after RVS. RVS-induced increases in voiding frequency are similar to other reports regarding several other animal models of stress including social defeat (4,15,46,74), nontraumatic immobilization/restraint (11,74), and WAS (14,54,62). We suggest that the 7-day RVS model has several advantages compared with other stress models.…”
Section: Rvs Induces Changes In Urinary Bladder Functionsupporting
confidence: 87%
“…Therefore, patients diagnosed with IC/BPS and other functional urinary tract disorders may have abnormalities in the HPA axis, and stress could contribute to bladder symptoms, including frequency, urgency, and/or pain, reported by these patient populations (47). The pathophysiology underlying stress-induced effects on micturition reflex function remain undetermined.The most well-established animal models of stress used to examine effects on urinary bladder structure and function include the resident-intruder model (15,22,74), immobilization stress (10, 11), water avoidance stress (WAS) (14,54,55,62), and electrical footshock (7,55). Although these stress paradigms produce bladder dysfunction and target tissue (i.e., urinary bladder) abnormalities similar to conditions like IC/BPS, the data in some cases are conflicting, and the stress models used in these studies may not be relevant to the variety of life stressors experienced by humans on a daily basis.…”
mentioning
confidence: 99%
“…In the chronic constriction injury model of neuropathic pain, WKY rats exhibited enhanced mechanical allodynia when compared to the Wistar rats (Zeng et al, 2008). Studies have also reported that hyperalgesia is exacerbated upon application of a water avoidance stress paradigm in WKY rats (Robbins et al, 2007).…”
Section: Wky Rat Model -Genetic Model Of Hyperalgesia Associated Withmentioning
confidence: 96%
“…SKS uygulanan grupta serum kortizol seviyesinde istatistiksel olarak anlamlı bir artış tespit edildiğinden, çalışmamızda kullandığımız kaygı stres modelinin çalışan ve geçerli bir model olduğu gösterilmiştir. Stresin ağrılı bir mesane hastalığı olan İS'in patofizyolojisinde önemli bir rol oynadığı birçok klinik ve deneysel çalışmada gösterilmiştir (3,4). SKS uygulanmış dişi sıçan mesane dokusuna ait ışık mikroskobik incelemelerde, lamina propriyada polimorf nüveli lökosit infiltrasyonu, ürotelyum hücrelerinde hasar, GAG tabakasında düzensizlik ve granüllü ve degranüle olmuş mast hücre artışı izlenmiştir (17,21,22).…”
Section: Discussionunclassified
“…Oksitosin grubuna (OT) 5 gün subkutan (sc) 5 µg/kg oksitosin uygulanmıştır. 4. Kronik Stres +Oksitosin grubuna (KS+OT) kronik stres boyunca 5μg /kg oksitosin sc uygulanmıştır.…”
Section: Original Research öZetunclassified